Barriers to effective feedback in undergraduate medical education: case study from Saudi Arabia - Alrebish, Saleh Ali (International Journal of Health Sciences, 2018)
Objectives: Students’ feedback is an essential source of data for evaluation and improvement of quality of education. Nonetheless, feedback may be routinely practiced for accreditation purposes and it is considered as a ritual employed by students, which makes its effectiveness questionable. The aim of this study is to explore and analyze the students’ perceptions about the importance of feedback and the barriers for effective feedback and suggest a proper ways to overcome these barriers. Methodology: This cross-sectional, anonymous, questionnaire-based study was conducted in the College of Medicine, Qassim University. 299 medical students, composed of 185 male and 114 female, from different levels during December, 2015 participated. Mean value, standard deviation, and proportion were used to quantify the quantitative and categorical study and outcome variables. Results: 47% of students responded to the questionnaire with more participation of juniors and females. Half of students believed that feedback is not important, and agreed for the presence of barriers for effective feedback. 5th level students exhibited higher resistance for participation in feedback, and there was a significant difference between male and female students. Promisingly, most of participant did not believe the presence cultural barrier for feedback. Conclusion: Saudi medical students are willing to involve in effective feedback. Some barriers, that make feedback practiced as tokenistic, are present. They can be overcome through proper orientation and appropriate closing the loop with response to the feedback declared to students. Further investigation is needed to explore barriers to feedback in higher education settings, and help designing an approach to enhance effectiveness of feedback on national level.